2020
DOI: 10.1097/pec.0000000000002313
|View full text |Cite
|
Sign up to set email alerts
|

Low Concordance Between Pediatric Emergency Attendings and Pediatric Residents for Predictors of Serious Intracranial Injury

Abstract: Objectives: Minor head trauma is a common cause of pediatric emergency room visits. The Pediatric Emergency Care Applied Research Network head trauma clinical decision rules (PECARN-CDR) are designed to assist clinicians in determining which patients require imaging. However, only minimal data are available on the accuracy of residents' assessments using PECARN-CDR. Prior research suggests that trainees often come to erroneous conclusions about pediatric head trauma. The objective of the present study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, despite poor concordance between attending and intern risk stratification between groups (23% vs. 17%), interns in both groups frequently made the correct clinical decision for neuroimaging when compared against the attending decision, indicating that both arms were able to effectively apply their knowledge of the PECARN head trauma algorithm to patient care. This may indicate that the PECARN rule itself is more easily applied than anticipated despite variations in learner knowledge and even risk stratification 27 . We concluded that application of the PECARN rule works well despite educational variances.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, despite poor concordance between attending and intern risk stratification between groups (23% vs. 17%), interns in both groups frequently made the correct clinical decision for neuroimaging when compared against the attending decision, indicating that both arms were able to effectively apply their knowledge of the PECARN head trauma algorithm to patient care. This may indicate that the PECARN rule itself is more easily applied than anticipated despite variations in learner knowledge and even risk stratification 27 . We concluded that application of the PECARN rule works well despite educational variances.…”
Section: Discussionmentioning
confidence: 76%
“…This may indicate that the PECARN rule itself is more easily applied than anticipated despite variations in learner knowledge and even risk stratification. 27 We concluded that application of the PECARN rule works well despite educational variances. Our study suggests that simulation-based education could potentially be used where clinical application of decision rules is poor.…”
Section: Discussionmentioning
confidence: 79%